Ports 2022. papers from sessions of the 16th triennial international conference, September 18-21, 2022, Honolulu, Hawaii - Erbland, Philip, J.; Jones, Bryan N. (American Society of Civil Engineers, 2022)
This collection contains selected papers from the 16th Triennial International Conference, held in Honolulu, Hawaii. Eighty-four papers are included in this volume on the following topics: simulation and modeling of port operations; berthing, mooring, and bulkheads; rehabilitation and repair of facilities; fender systems; piers and wharves; seismic and storm surge effects; and infrastructure maintenance and upgrades. These papers will be of interest to both practitioners and researchers in the area of port engineering.